2016
DOI: 10.1007/s00429-016-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

Myelination of the right parahippocampal cingulum is associated with physical activity in young healthy adults

Abstract: Recent evidence suggests that individual differences in physical activity (PA) may be associated with individual differences in white matter microstructure and with grey matter volume of the hippocampus. Therefore, this study investigated the association between PA and white matter microstructure of pathways connecting to the hippocampus. A total of 33 young, healthy adults underwent magnetic resonance imaging (MRI). High angular resolution diffusion-weighted imaging and multi-component relaxometry MRI scans (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…Walther and colleagues [Walther et al, ] investigated young HP (age: 31.2 ± 6.5 years) and found that motor activity levels were negatively associated with FA variations within the left corticobulbar tract, the right posterior corpus callosum, and the left superior longitudinal fasciculus. In a more recent study by Bracht and colleagues [Bracht et al, ] on a sample of young HP (age: 24.5 ± 4.2 years), physical activity was significantly associated with myelin water fraction in the right parahippocampal cingulum. A persimonious explanation for these findings and the results of the present study is that not only one but a number of very different WM sub‐compartments variations within the motor relevant fiber tracts may contribute to quantitative and qualitative motor performance in young HP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Walther and colleagues [Walther et al, ] investigated young HP (age: 31.2 ± 6.5 years) and found that motor activity levels were negatively associated with FA variations within the left corticobulbar tract, the right posterior corpus callosum, and the left superior longitudinal fasciculus. In a more recent study by Bracht and colleagues [Bracht et al, ] on a sample of young HP (age: 24.5 ± 4.2 years), physical activity was significantly associated with myelin water fraction in the right parahippocampal cingulum. A persimonious explanation for these findings and the results of the present study is that not only one but a number of very different WM sub‐compartments variations within the motor relevant fiber tracts may contribute to quantitative and qualitative motor performance in young HP.…”
Section: Discussionmentioning
confidence: 98%
“…In elderly individuals, WM changes might be the result of different neuroplastic processes [Tseng et al, 2013], whereas young individuals exhibit predominantly myelination changes which have only subtle effects on FA [Bracht et al, 2016;Song et al, 2002]. Therefore, it is not possible to robustly answer the question whether sub-threshold depressive symptoms that might be present in this study group consisted of young healthy individuals had an influence on WM.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Very few studies have yet used more myelin-specific MR measures to assess relationships between physical activity and white matter microstructure. A recent, cross-sectional study in young adults found a positive correlation between MWF in the right parahippocampal cingulum and amount of physical activity monitored over three days (Bracht et al, 2016). There is need for more interventional studies in humans to assess whether such relationships reflect a causal influence of physical activity on myelination.…”
Section: Imaging Experience-dependent Myelin Plasticity In Humansmentioning
confidence: 99%
“…Furthermore, while controls exhibited an association between actigraphy levels and perfusion within core motor areas, such as the cingulate motor area and external globus pallidus, this association was not found in MDD subjects [25]. MPI Walther has also shown that activity levels in MDD patients and controls are linked with white matter microstructure of motor pathways and limbic pathways [26,27,61,62]. However, the associations between white matter properties and activity differed between patients and controls within cortico-cortical motor pathways, suggesting that structural connectivity alterations between prefrontal and premotor/motor cortices hamper spontaneous motor behavior in patients [26].…”
Section: Brain Correlates Of Actigraphymentioning
confidence: 99%